(untitled) (Repertorio Científico, 2024)
This work presents in a systematic and descriptive way a practice of texture analysis of fruits and vegetables using a texture analyzer, through a remote laboratory, whose environment allowed students to carry out several activities typical of the experimental test: configuration of the equipment and material analysis, experimental analysis process, obtaining experimental data. The methodology included the design and application of a questionnaire supported by Likert scale statements to measure the perception of learning theoretical-practical knowledge of texture analysis, which was applied to a sample of seven students from the Postharvest Management course of the chair of Agroindustry, State Distance University, the usability of the remote laboratory was determined in terms of access and ease or difficulty of use. The results show a positive response towards the learning and use of the remote laboratory by the students. And as an opportunity to improve the experimental trial, the provision of additional complementary material that supports the resources of the remote laboratory environment is proposed.